2017
DOI: 10.3390/nu9020095
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Sources of Phosphorus among Adults in the United States: Results from NHANES 2001–2014

Abstract: Interest in the health effects of dietary phosphorus is burgeoning, yet sources and trends in phosphorus consumption have not been well characterized. We describe trends in and primary sources of dietary phosphorus in a nationally representative sample of 34,741 US adults, 20+ years old (NHANES 2001–2014). Dietary sources of phosphorus were estimated in nine food groups and 26 food categories. Phosphorus consumption was expressed in absolute intake, phosphorus density, and proportion contributed by dietary sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
70
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(76 citation statements)
references
References 32 publications
4
70
0
2
Order By: Relevance
“…Rapidly absorbed as hormonal mechanisms attempt to maintain the serum inorganic phosphate concentration within narrow limits; exposure of cells to a brief high-serum inorganic phosphorus concentration potentially signals alterations in cell functions that lead to deleterious effects; phosphate binds calcium, thus preventing calcium from binding to bile acids (27,28) Grains, meat, milk (29) Sodium Decreases 11b-hydroxysteroid dehydrogenase type 2 activity in the colonic epithelium, slowing down cortisol catabolism (19,30,31); may impair immune defenses in the colon epithelium the analytic cohort, leaving 35,221 participants, including 1,731 who developed colorectal cancer during follow-up, for analysis.…”
Section: Phosphorusmentioning
confidence: 99%
“…Rapidly absorbed as hormonal mechanisms attempt to maintain the serum inorganic phosphate concentration within narrow limits; exposure of cells to a brief high-serum inorganic phosphorus concentration potentially signals alterations in cell functions that lead to deleterious effects; phosphate binds calcium, thus preventing calcium from binding to bile acids (27,28) Grains, meat, milk (29) Sodium Decreases 11b-hydroxysteroid dehydrogenase type 2 activity in the colonic epithelium, slowing down cortisol catabolism (19,30,31); may impair immune defenses in the colon epithelium the analytic cohort, leaving 35,221 participants, including 1,731 who developed colorectal cancer during follow-up, for analysis.…”
Section: Phosphorusmentioning
confidence: 99%
“…However, the average phosphorus intake of U.S. adults over the age of 20 is 1399 mg/d – approximately 2.5 times the EAR and twice the RDA. McClure et al (5) recently described the trends in dietary phosphorus intake in U.S. adults between 2001–2014 from NHANES data, as well as the percent contributions of various categories of foods to total phosphorus consumption. Although total phosphorus consumption has risen over the recent decades (6), intakes were relatively stable between 2001 and 2014 (5).…”
Section: Phosphorus As An Essential Nutrientmentioning
confidence: 99%
“…McClure et al (5) recently described the trends in dietary phosphorus intake in U.S. adults between 2001–2014 from NHANES data, as well as the percent contributions of various categories of foods to total phosphorus consumption. Although total phosphorus consumption has risen over the recent decades (6), intakes were relatively stable between 2001 and 2014 (5). Grains were the largest contributor to total dietary phosphorus intake, accounting for 29.3% of intake.…”
Section: Phosphorus As An Essential Nutrientmentioning
confidence: 99%
“…McClure and et al [1] also refer to the paper of St-Jules and coworkers [15] that reviewed urinary phosphorus excretion in four human intervention studies that were not, however, designed to compare phosphorus bioavailability by food source. Despite the fact that St-Jules et al found some discrepancies in the digestibility of food additive phosphates in those studies, they state that additives are the major dietary phosphorus source that can be eliminated without impairing diet quality of kidney patients [15].…”
mentioning
confidence: 99%